Corneal hysteresis as a predictor of glaucomatous optic neuropathy progression - N.I. Kurysheva; E.O. Shatalova; L.V. Lepeshkina (РМЖ "Клиническая офтальмология", 2019)
N.I. Kurysheva1, E.O. Shatalova2, L.V. Lepeshkina1 1 Burnazyan Federal Medical Biophysical Center of Federal Medical Biological Agency,   Moscow, Russian Federation 2 LLC “Doctor Shatalov Clinic”, Orekhovo-Zuyevo, Russian Federation Aim: to determine the role of corneal hysteresis (CH) as the predictors of glaucomatous optic neuropathy (GON) progression in a comparative aspect with morpho-functional parameters. Patients and Methods: 128 (173 eyes) patients with primary open-angle glaucoma (POAG) and primary angle-closure glaucoma (PACG) were observed in a retrospective study. All patients were divided into two groups: group 1 — with no GON progression, group 2 — with GON progression. The observation period lasted 7 years. Corneal-compensated intraocular pressure (IOP) and CH, as well as morpho-functional parameters: perimetric indexes (MD, PSD), retinal nerve fiber layer (RNFL), ganglion cell complex (GCC), global loss volume (GLV) and focal loss volume (FLV) — were examined as the predictors of GON along with other clinical parameters. Results: the study determined the diagnostic significance of the parameters as predictors of glaucomatous optic neuropathy progression — AUC (estimation of the area under the characteristic ROC-curve). It was found that the groups statistically significantly differ by the following indicators: corneal hysteresis (AUC 0.640±057, p=0.006), age (AUC 0.612±0.051, p=0.006), MD (AUC 0.710±0.066, p=0.001), PSD (AUC 0.681±0.066, p=0.006), RNFL (AUC 0.620±0.041, p=0.007) and FLV (AUC 0.617±0.050, p=0.008). Conclusion: despite the fact that most researchers agree that IOP is a leading factor in the progression of the disease, in recent years, a thesis that the corneal hysteresis is more prognostically important is heard more often. Thus, in the course of the study, the initial low level of CH, but not the initial IOP, was associated with the GON progression. Other significant factors were the age of patients and the degree of glaucomatous lesion, characterized by perimetric indexes and the retinal nerve fiber layer, as well as the focal loss volume of its ganglion cell complex. Key words: corneal hysteresis, predictors of progression, glaucomatous optic neuropathy. For citation: Kurysheva N.I., Shatalova E.O., Lepeshkina L.V. Corneal hysteresis as a predictor of glaucomatous optic neuropathy progression. RMJ “Clinical ophthalmology”. 2018;4:168–173.